The Study on Datum Temperature of Concrete in Tropical Climate – Malaysia Case - Loh, Khang Jia; Jamaluddin, Norwati (Journal of Structural Monitoring and Built Environment, 2024)
This study investigates the datum temperature for concrete maturity in Malaysia’s tropical climate, aiming to enhance concrete strength prediction. Traditional methods are time-consuming, and the maturity method offers a viable alternative. The research establishes a customized datum temperature considering regional variability. Mortar samples of M25 and M35 were cured at 22°C, 27°C, and 32°C for 32 days, with compressive strength measured according to ASTM C1074 guidelines. Results indicated higher curing temperatures accelerated early strength development. For M25 mortar, compressive strength increased from 8.45 N/mm² at 22°C on day 1 to 28.07 N/mm² on day 32, and from 11.28 N/mm² to 28.76 N/mm² at 32°C. For M35 mortar, strength rose from 10.71 N/mm² at 22°C on day 1 to 37.20 N/mm² on day 32, and from 14.64 N/mm² to 38.08 N/mm² at 32°C. Despite variations in early strength gain, all samples achieved similar ultimate strength. The datum temperatures identified were 3.1°C for M25 and 3.5°C for M35, significantly higher than the ASTM C1074 range of -10°C to 0°C, underscoring the need for localized testing for accurate strength assessments. This study highlights the necessity of specific datum temperatures to improve the precision and effectiveness of concrete maturity methods in tropical climates.